2020
DOI: 10.1093/ecco-jcc/jjaa260
|View full text |Cite
|
Sign up to set email alerts
|

Ustekinumab for Extra-intestinal Manifestations of Inflammatory Bowel Disease: A Systematic Literature Review

Abstract: Background and Aims Extra-intestinal manifestations [EIMs] are frequent in patients with inflammatory bowel diseases [IBD] and are challenging conditions to manage. Tumour necrosis factor alpha antagonists [anti-TNFα] are recognised as the primary therapeutic option. We aimed to summarise evidence on the efficacy of ustekinumab for the treatment of EIMs. Methods We searched in PubMed, Cochrane Library, and Web of Science, up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 44 publications
0
40
0
6
Order By: Relevance
“…In a recent systematic review, evidence was provided that ustekinumab can be effective for IBD-associated peripheral arthritis (as well as skin EIMs), but not in axSpA. 54 Tofacitinib is an oral, small molecule that inhibits mainly JAK1 and JAK3 and is available and approved for the treatment of moderately to severely active UC, as well as rheumatoid arthritis and PsA. Phase 3 trials are under way to establish its safety and efficacy in AS.…”
Section: Additional Therapeutic Considerationsmentioning
confidence: 99%
“…In a recent systematic review, evidence was provided that ustekinumab can be effective for IBD-associated peripheral arthritis (as well as skin EIMs), but not in axSpA. 54 Tofacitinib is an oral, small molecule that inhibits mainly JAK1 and JAK3 and is available and approved for the treatment of moderately to severely active UC, as well as rheumatoid arthritis and PsA. Phase 3 trials are under way to establish its safety and efficacy in AS.…”
Section: Additional Therapeutic Considerationsmentioning
confidence: 99%
“…The available data on vedolizumab do not support its efficacy in this indication. With regard to ustekinumab, some premises exist to suggest its efficacy, although evidence of higher scientific value is still to be obtained [298][299][300]. Upon the diagnosis of CD, a complete medical history should be collected including information on the history of infectious diseases and protective vaccinations.…”
Section: Ix7 Arthropathy Associated With CDmentioning
confidence: 99%
“…UST has also demonstrated clinical efficacy in chronic plaque psoriasis or active psoriatic arthritis treatment 14,15 . A systematic review on UST for treatment of EIMs in IBD suggested that UST was effective, in particular for treatment of dermatologic manifestations such as psoriasis, PG and EN, and rheumatologic manifestations such as arthralgias and psoriatic arthritis 16 . However, the existing literature is limited due to mainly retrospective evaluations (eight of nine studies), small sample sizes (total of 254 patients included in the review) and lack of comparator groups.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 A systematic review on UST for treatment of EIMs in IBD suggested that UST was effective, in particular for treatment of dermatologic manifestations such as psoriasis, PG and EN, and rheumatologic manifestations such as arthralgias and psoriatic arthritis. 16 However, the existing literature is limited due to mainly retrospective evaluations (eight of nine studies), small sample sizes (total of 254 patients included in the review) and lack of comparator groups. This post hoc analysis of UNITI-1/2 and IM-UNITI aimed to evaluate the efficacy of UST in treatment of EIMs in moderate-severe CD patients.…”
Section: Introductionmentioning
confidence: 99%